PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI HOURS COFFEE AND MORE JAKARTA - Mariyana; Ricky Talumantak (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study was to determine the effect of perceived price, product quality, and promotion on purchasing decisions at Hours Coffee And More Jakarta. The sampling technique used was non-probability sampling with purposive sampling method obtained 80 consumers as respondents. The analysis method used is multiple linear regression analysis. The results showed that partially perceived price had no influence on purchasing decisions, partially product quality had a positive influence on purchases, and partially promotion had a promotional influence on purchasing decisions. And simultaneously price perceptions, product quality and promotion have a positive influence on purchasing decisions.